Implication of the Influence of Work Motivation and Leadership on Organizational Behavior in the Education Office of Labuhanbatu Regency - Heru Syahputra; Yudi Prayoga; Pitriyani Pitriyani (Garuda Prestasi Nusantara Consulting, 2022)
The purpose of this study was to determine the implications of the influence of work motivation and leadership on organizational behavior in the Education Office of Labuhanbatu Regency. This research was conducted at the Labuhanbatu District Education Office. The object of this research is work motivation, leadership, and organizational behavior. The number of samples in this study was 34 respondents. Data were collected using a questionnaire with a Likert scale unit of measurement. The data analysis in this study used multiple linear regression analysis and for hypothesis testing was used the F-test and t-test assisted by the SPSS version 20 test tool. The results showed that work motivation and leadership together influence the organizational behavior in the Education Office. Labuhanbatu Regency, and partially prove that work motivation and leadership also have implications for organizational behavior in the Labuhanbatu Regency Education Office.